Pengembangan Video Pembelajaran Berbantuan Aplikasi Sparkoll Videoscribe - Ahmad Fadillah; Westi Bilda (Jurnal Gantang, 2019)
. This research was conducted at the University of Muhammadiyah Tangerang on the academic year 2018-2019 Mathematics Education study program. The purpose of this research was to develop learning videos with videoscribe sparkoll application. The methods used od this research were Research and Development (R&D). The stages used are field observation, data collection, product design, expert validation, product revision, small class trials, data analysis, and final products. based on the results of the validation of the experts by getting eligible criteria for each criterion namely 78% and 78.7% and the results of small-scale trials by getting a positive response and eligible criteria which is 75.5%.